Seed yam (Dioscorea rotundata Poir) production, storage, and quality in selected yam zones of Nigeria - Asiedu, Robert; Akoroda, M.O.; Aighewi, B.A. (2002)
The unavailability of good quality seed yams (Dioscorea rotundata Poir) is frequently cited to be responsible for the slow rate of growth or decline in yam production. Current production and storage practices, as well as quality of seed yams in 35 villages of Oyo North, Asaba, Lokoja, and Lafia areas of the yam belt of Nigeria were studied in a survey involving 299 farmers that were interviewed using a questionnaire. Over 57% of the farmers used only seed yams from their farms for propagation. All farmers practiced double harvesting in combination with some other traditional methods of seed production. Between 50.0 and 65.0% of farmers in Asaba treated seed yams with purchased chemicals before planting to protect against yam beetle attack, while in other locations less than 35.0% did any form of treatment. Storage in situ or planting shortly after harvest was widely practiced in Oyo North, Lokoja and Lafia areas. In Asaba, storage was done for longer periods in yam barns. The yam beetle and scale insects caused much damage to seed yams in Asaba and Lokoja, respectively. Forty seven to 90% of farmers had a combination of pests and rots on their seed yams. The high level of loss and poor quality of seed yams in some yam zones of Nigeria are due to the pests and diseases, which are favoured by current production and storage, practices.